Establishing and Assessing of a Leak Collection System Analysis Method by Computational Fluid Dynamics - Dae Kyung Choi; Won Man Park; Woo-Shik Kim; Dong-Jin Euh; Tae-Soon Kwon; Choengryul Choi (Modelling and Simulation in Engineering)
Small leaks within a nuclear power plant can escalate into significant leaks, leading to plant shutdown and substantial losses if operational limits are exceeded. Thus, the demand for systems that can rapidly detect minor leaks is increasing. Current research seeks to address this need. Understanding the thermal–hydraulic features of these systems is crucial for their evolution. In this study, we designed a numerical analysis process to evaluate a prototype leak detection system simulator. We devised a numerical model to simulate leaks and subsequently conducted a bifurcated computational fluid dynamics analysis to assess its viability. First, we examined the leak dynamics within the insulation, focusing on the effects of the gap between the pipe’s insulation and its external casing. The findings from the initial analysis informed the conditions for studying the collection loop. The assessment highlighted a shift in relative humidity downstream of the collection loop, mirroring experimental observations. The results suggest that the newly developed small leak detection system can effectively detect leaks by collecting the escaping fluid through a collection loop and analyzing variations in relative humidity when a small leak occurs in the high-pressure piping of a nuclear power plant. These findings have been instrumental in developing a collection loop experimental apparatus, which will further elucidate the heat transfer dynamics during its operation.